Aptamers and antibodies: rivals or allies in cancer targeted therapy? - Lisa Agnello; Simona Camorani; Monica Fedele; Laura Cerchia (Open Exploration Publishing Inc., 2021)
The goal of an efficacious cancer therapy is to specifically target diseased cells at high accuracy while sparing normal, healthy cells. Over the past three decades, immunotherapy, based on the use of monoclonal antibodies (mAbs) directed against tumor-associated antigens, to inhibit their oncogenic function, or against immune checkpoints, to modulate specific T cell responses against cancer, has proven to be an important strategy for cancer therapy. Nevertheless, the number of mAbs approved for clinical use is still limited because of significant drawbacks to their applicability. Oligonucleotide aptamers, similarly to antibodies, form high-affinity bonds with their specific protein targets, thus representing an effective tool for active cancer targeting. Compared to antibodies, aptamers' use as therapeutic agents benefits from their low size, low/no immunogenicity, simple synthesis and design flexibility for improving efficacy and stability. This review intends to highlight recently emerged applications of aptamers as recognition elements, from biomarker discovery to targeted drug delivery and targeted treatment, showing aptamers' potential to work in conjunction with antibodies for attacking cancer from multiple flanks.